ENERGY POTENTIAL ASSESSMENT OF SOLAR AND WIND RESOURCES IN SYRIA - Ramadan, Amer; Elistratov, Viktor (Journal of Applied Engineering Science, 2018)
The present paper aims to determine the energy potential of solar and wind resources in Syria. To achieve this goal, the first calculation method was developed for assessing the average total gross and technical potential of solar energy falling on a horizontal surface in Syria using electronic resource (Solar Atlas for the Mediterranean). The second calculation method was developed for estimating the average total gross and technical potential of wind energy in Syria using electronic resource (Global Wind Atlas). The results indicated: firstly, that the average total gross and technical potential of solar energy on a horizontal surface in Syria were estimated, respectively, 345406 TWh/year and 55265 TWh/year. Secondly, the average wind power at the height of 50 m and the average total gross potential of wind energy in Syria were estimated, respectively, 31,2 TW and 273533 TWh /year. Finally the average technical potential of wind energy using 1% , 2% , 3% , 4% , 5% of the total area of Syria was estimated, respectively, 129 , 258 , 387 , 516 , 644 TWh /year.